To describe the given sequence \( 92, 93, 94, 95, \ldots \), we can see that it is an arithmetic sequence where the first term \( a_1 \) is 92 and the common difference \( d \) is 1 (since each term increases by 1).
The general expression for the \( n \)-th term of an arithmetic sequence can be defined as:
\[ a_n = a_1 + (n - 1) \cdot d \]
Substituting \( a_1 = 92 \) and \( d = 1 \):
\[ a_n = 92 + (n - 1) \cdot 1 \]
This simplifies to:
\[ a_n = 92 + (n - 1) = 92 + n - 1 = n + 91 \]
Thus, the expression for the \( n \)-th term of the sequence is:
\[ a_n = n + 91 \]
Now, to find the 18th term, we substitute \( n = 18 \) into the expression:
\[ a_{18} = 18 + 91 = 109 \]
Thus, the answers are:
\[ a_n = n + 91 \] \[ a_{18} = 109 \]